Anemia and blood transfusions in myelofibrosis: economic and organizational impact on Italian patients, caregivers and hospitals - Palandri, Francesca; Inzoli, Alessandro; Barone, Antonella; Dordoni, Daniela; Formenti, Elisa; Corradini D’Elia, Giorgio; Rabsiun Aramburu, Victoria Lucia; Palumbo, Giuseppe Alberto; Breccia, Massimo (Frontiers in Oncology, 2025)
IntroductionAnemia management in myelofibrosis (MF) remains a major challenge, often resulting in blood transfusions as the condition progresses. The BEAT project aimed to quantify the economic and organizational burden of anemia and transfusions in MF patients in Italy from the patient and hospital perspectives.MethodsData were collected from two primary sources: (i) semi-structured interviews with 13 hematologists and 1 transfusionist from 13 Italian MF reference centers; (ii) an online questionnaire completed by 191 patients distributed by AIPAMM (Italian Association of Patients with Myeloproliferative Diseases). Patients were categorized into 9 patient types based on the Dynamic International Prognostic Scoring System (DIPSS), anemia status, and need for transfusions. The collected data was used to feed an analytical model to quantify time and costs for patients, caregivers and the healthcare system over one year for managing MF, MF-related anemia, and transfusion care for each patient type.ResultsTransfusion dependent patients spend, on average, six times more time on MF care compared to non-anemic patients (133.1 vs 20.9 hours/year). Transfusion-related hospital visits represent a major burden, with waiting times accounting for 44% of total access time (about 7.3 hours). Annual hospital management time and estimated costs per patient are 17.0 vs. 5.2 vs. 3.5 hours/year, and €6,603 vs. €249 vs. €165/year for transfusion dependent, anemic non-transfusion dependent, and non-anemic patients, respectively. Indirect social costs for transfusion dependent patients (€2,332) are estimated to be six times greater than those for non-anemic patients (€367). Patient surveys confirmed the significant impact of transfusion dependency on work, social, and daily life, with scores of 4.5/5 for work and over 4/5 for social and daily life.DiscussionThese findings highlight the urgent need for optimizing MF-related anemia and transfusion management to help mitigate the economic strain on healthcare systems and lessen the time-related and emotional impact on patients and caregivers.